1965
DOI: 10.3189/s0022143000018694
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Mass Budget of Arctic Pack-Ice Floes

Abstract: The processes of melting, freezing, precipitation, evaporation and condensation were considered in the computation of the mass budget of an ice floe in the northern Chukchi Sea. It was bound that condensation and evaporation contribute negligible amounts, and that melting accounted for the largest loss from the upper surface of the floe. From an original mass of 270 g. cm.−2 a unit ice column lost 9.2 g. cm.−2 by melting of snow and 35.2 g. cm.−2 by melting of ice during the melt season. During the freezing pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 1 publication
3
30
0
Order By: Relevance
“…Assuming the 2013 IMB is representative of unponded regions and that our estimates include ponded ice melt we can then differentiate the contribution of ponded versus nonponded melt using our total melt estimate of 1.3 m. Using a range of melt pond coverage for MYI between 15% and 24% (Nicolaus et al, ; Perovich et al, ; Rabenstein et al, ) results in a total melt rate for ponded ice between 1.5 and 2.4 m. This range is highly sensitive to variations in the pond coverage estimates. Nevertheless, it is consistent with the possible ~1.9 m of total melt for ponded ice considering ice surface melt of up to ~1 m (Hanson, ; Untersteiner, ) and bottom ice melt of up to 0.92 m within the PIZ (Perovich & Richter‐Menge, ). These results emphasize the potential for large floe‐scale variability in melt rates that may not be captured by single IMB observations, particularly if these observations are only from hummock ice and do not include melt ponds or vice versa.…”
Section: Discussionsupporting
confidence: 84%
“…Assuming the 2013 IMB is representative of unponded regions and that our estimates include ponded ice melt we can then differentiate the contribution of ponded versus nonponded melt using our total melt estimate of 1.3 m. Using a range of melt pond coverage for MYI between 15% and 24% (Nicolaus et al, ; Perovich et al, ; Rabenstein et al, ) results in a total melt rate for ponded ice between 1.5 and 2.4 m. This range is highly sensitive to variations in the pond coverage estimates. Nevertheless, it is consistent with the possible ~1.9 m of total melt for ponded ice considering ice surface melt of up to ~1 m (Hanson, ; Untersteiner, ) and bottom ice melt of up to 0.92 m within the PIZ (Perovich & Richter‐Menge, ). These results emphasize the potential for large floe‐scale variability in melt rates that may not be captured by single IMB observations, particularly if these observations are only from hummock ice and do not include melt ponds or vice versa.…”
Section: Discussionsupporting
confidence: 84%
“…Ice melting, brine flushing, and drainage of melt pond lead to the formation of a stable fresh water layer at the ice‐ocean interface. These fresh water lenses, called under‐ice melt ponds by Hanson [1965], are usually trapped under thinner ice areas or in depressions in the bottom of thicker ice. Within this fresh water layer, we observed a marked undersaturation down to 5 μ atm (Figure 4c).…”
Section: Discussionmentioning
confidence: 99%
“…Third, meltwater gets discharged under the ice through highly permeable ice or flaws and along floe margins. This meltwater can be retained under thin ice or in bottom depressions, leading to fresh water lenses which Hanson [1965] calls “under‐ice melt ponds.” At the interface between this (light) fresh water and the underlying (dense) salt water, double‐diffusive convection of heat and salt occurs, leading to the formation of underwater ice, called false bottoms [ Untersteiner and Badgley , 1958; Hanson , 1965; Martin and Kauffman , 1974; Cherepanov et al , 1989; Eicken , 1994; Eicken et al , 2002]. Nansen [1897] noted that this is the only process by which significant amounts of new ice can be formed during the summer.…”
Section: Introductionmentioning
confidence: 99%
“… Jeffries et al [1995] found traces of false‐bottom ice in 22 of 57 cores analyzed in the Beaufort Sea, corresponding to an areal coverage of false bottoms of at least 10% of the level ice for an average ice age of 4 years. Hanson [1965] estimated that under‐floe melt ponds and false bottoms covered half of the flow bottom of the drifting station “Charlie.” This probably represents an upper bound of the areal coverage of false bottoms, and Hanson's measurements may have been affected by artificial drainage in the vicinity of an ice camp. However, as Jeffries et al [1995] point out, the possibility that ice growth in under‐ice melt ponds is common and not an oddity is consistent with the interpretation of data obtained by submarine sonar measurements [ Wadhams and Martin , 1990].…”
Section: Introductionmentioning
confidence: 99%